Alström syndrome: A case report of the Polish family and a brief review of the differential diagnosis - Wicher, Katarzyna; Bajon, Tomasz; Wawrocka, Anna; Skorczyk-Werner, Anna; Niedziela, Marek; Krawczynski, Maciej Robert (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Alström syndrome (ALMS) is an autosomal recessive disorder caused by mutations in the ALMS1 gene. We report two brothers from Poland, initially diagnosed with cone-rod dystrophy. Analysis of the history and physical examination gave rise to the suspicion that the patients suffered from ALMS. Mutation analysis of ALMS1 gene revealed in both cases two heterozygous nonsense mutations: c.8164C>T (p.Arg2722*) in exon 10 and c.11207C>A (p.Ser3736*) in exon 16, what confirmed the diagnosis. In the context of our case, we review the genetic and clinical features of ALMS, focusing particular on the differential diagnosis and the necessity of molecular testing.